An Aminoisoxazole‐Based Proto‐RNA - Felix Xu; Dr. Stefan Wiedemann; Dr. Jonas Feldmann; Dr. Sidney Becker; Prof. Dr. Thomas Carell (ChemistryEurope, 2023)
Abstract The RNA world hypothesis predicts that life started with the development of replicating and catalytically active RNA, which evolved in a process of molecular evolution to increasingly complex chemical structures. RNA is, however, so complex that it has most likely formed from a precursor (proto‐RNA) that was more easily accessible in a prebiotic world. Recently, 3‐aminoisoxazoles (IO3) were identified as building blocks that can form under prebiotic conditions and can rearrange to give the nucleoside cytidine (C). The present study shows that the constitutional isomer 5‐aminoisoxazole (IO5) can undergo the same reaction to give uridine (U). Both compounds (IO3 and IO5), if embedded in RNA, react selectively to C and U, which are the main pyrimidine nucleosides of the genetic system. Importantly, the stereochemical outcome of the IO5 reaction in RNA depends on the neighboring bases. If they are β‐configured RNA nucleosides, the reaction proceeds with high selectivity to give exclusively the β‐configured U RNA base (anomeric control).